Ethnomedicinal Plants Used by the ethnic Communities of Tinsukia District of Assam, India - Buragohain*, Jitu (Recent Research in Science and Technology, 2011)
An ethnobotanical study focused on medicinal utility of plants was carried out among the ethnic communities of Tinsukia district of upper Assam with aims to document the traditional knowledge of the medicinal plants used in various ailments. The information was based on normal conversation, interview and discussion with local herbal practitioners, elderly men and women of different tribal communities. In this study, a total of 175 plant species belonging to 76 families were described which have been used in the treatment of around 56 diseases. Herbs, shrubs and trees were the dominant category of the plants. Most frequently medicated claims were stomach ailments, gynaecological problems, lung and respiratory diseases, cuts and wounds, skin diseases, urinary troubles and as well as their use as blood purifier. The most cited family was Euphorbiaceae, the most widely used plant part was the leaf and the most common mode of administration was decoction. All these claims need to be subjected to both phyto- and pharmaco-chemical investigations to discover the potentiality of these plants and plant parts as drugs.